2011
DOI: 10.1161/circulationaha.110.014860
|View full text |Cite
|
Sign up to set email alerts
|

Profibrinolytic, Antithrombotic, and Antiinflammatory Effects of an Insulin-Sensitizing Strategy in Patients in the Bypass Angioplasty Revascularization Investigation 2 Diabetes (BARI 2D) Trial

Abstract: Background Effects were compared in patients in the Bypass Angioplasty Revascularization Investigation 2 Diabetes (BARI 2D) trial of 2 mechanistically different strategies for treatment of hyperglycemia, insulin-sensitizing and insulin-providing strategies, on biomarker profiles reflecting the balance between fibrinolysis and thrombosis and the intensity of inflammation implicated in diabetic vasculopathy. Methods and Results A total of 2368 patients with type 2 diabetes mellitus and clinically stable, angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 40 publications
4
66
0
3
Order By: Relevance
“…Sobel et al (15) reported that, in BARI 2D subjects, IS as opposed to IP treatment led to changes in biomarker profiles that were indicative of a profibrinolytic, antithrombotic, and antiinflammatory state. Peroxisome proliferator-activated receptors are widely expressed in the kidney, and peroxisome proliferator-activated receptor gamma agonists have renoprotective effects in experimental models of diabetic kidney disease (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Sobel et al (15) reported that, in BARI 2D subjects, IS as opposed to IP treatment led to changes in biomarker profiles that were indicative of a profibrinolytic, antithrombotic, and antiinflammatory state. Peroxisome proliferator-activated receptors are widely expressed in the kidney, and peroxisome proliferator-activated receptor gamma agonists have renoprotective effects in experimental models of diabetic kidney disease (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of BARI 2D by Chaitman et al found that in the CABG‐stratum patients who had greater atherosclerotic burden, the reduction of MI seen in patients randomized to revascularization was found to be significant only in those randomized to an IS treatment strategy 2. Sobel and colleagues subsequently evaluated the impact of IS and IP treatment strategies on fibrinolytic biomarker profiles in the BARI 2D trial 7. Although IP therapy was associated with greater PAI‐1 antigen and activity, these changes did not translate into any difference in outcomes in the overall trial.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin, tPA antigen, and PAI‐1 assays were performed by ELISA. The tPA activity was not measured because it complexes with excess PAI‐1 in plasma resulting in activity that is undetectable 7. PAI‐1 activity was assayed with a chromogenic substrate kinetic procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…He played an important role in the Bypass Angioplasty Revascularization Investigation 2 Diabetes (BARI-2D) trial, in which he showed that insulin-sensitizing treatment of diabetic patients altered the balance between thrombosis and fibrinolysis, favoring the latter. 5 At the time of his death, he had 2 peer-reviewed articles in press and 1 under review, the latter in Circulation! Burt was as talented a leader as he was as an investigator, clinician, educator, and editor.…”
mentioning
confidence: 99%